2017
DOI: 10.1016/j.jadohealth.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior Among Orphaned Adolescents in Western Kenya: A Comparison of Institutional- and Family-Based Care Settings

Abstract: Purpose This study sought to assess whether risky sexual behaviours and sexual exploitation of orphaned adolescents differed between family-based and institutional care environments in Uasin Gishu County, Kenya. Methods We analyzed baseline data from a cohort of orphaned adolescents aged 10–18 years living in 300 randomly-selected households and 19 Charitable Children’s Institutions. The primary outcomes were having ever had consensual sex, number of sex partners, transactional sex, and forced sex. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
(45 reference statements)
6
17
0
Order By: Relevance
“…Parent-like support and family-related environments might be associated with the positive outcomes of OSCAs within the CCIs (Atwoli et al 2014;Braitstein et al 2013;Embleton et al 2014Embleton et al , 2017, which are consistent with findings of other studies (Whetten et al 2009(Whetten et al , 2014 conducted in similar low-and middle-income countries. Some CCIs provided a positive environment where children were able to focus on their education, were provided with their basic needs, and formed long-term positive relationships.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Parent-like support and family-related environments might be associated with the positive outcomes of OSCAs within the CCIs (Atwoli et al 2014;Braitstein et al 2013;Embleton et al 2014Embleton et al , 2017, which are consistent with findings of other studies (Whetten et al 2009(Whetten et al , 2014 conducted in similar low-and middle-income countries. Some CCIs provided a positive environment where children were able to focus on their education, were provided with their basic needs, and formed long-term positive relationships.…”
Section: Discussionsupporting
confidence: 89%
“…We found that family-based care environments in UG County were less likely to be able to provide for children's basic material needs than were CCIs and may not be able to provide an adequate standard of living. This study, our other work, and our observations in UG County led to the study question for this paper (Atwoli et al 2014;Braitstein et al 2013;Embleton et al 2014Embleton et al , 2017.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…9,18 Microenvironment Level of SEM Many studies suggest adolescents who reside with at least one parent or identify with the views of their parents are less likely to engage in RSB. 32,33 Being an orphan 32 may lead to a low socioeconomic status for female youths and could compel the girls to indulge in transactional sex. 32 The majority of sexually active girls had multiple sexual partners, 20 or were involved in transactional sex, 21 and reported non-use or irregular use of condoms by most of the boyfriends or sexual partners.…”
Section: Individual Level Of Semmentioning
confidence: 99%